Origin and fate of the single‐island endemic moss Orthotrichum handiense. (14th December 2012) - Patiño, Jairo; Medina, Rafael; Vanderpoorten, Alain; González‐Mancebo, Juana M.; Werner, Olaf; Devos, Nicolas; Mateo, Rubén G.; Lara, Francisco; Ros, Rosa M.; Linder, Peter
Abstract Aim Our aims were: to determine the evolutionary origin of the single‐island endemic moss Orthotrichum handiense; to assess whether its endemicity results from a recent origin or founder event, a loss of dispersal ability, specific habitat requirements, or contraction of a formerly wider range; and to make predictions about its ability to face ongoing climate change. Location Fuerteventura, Canary Islands. Methods The evolutionary origin of O. handiense was determined by phylogenetic analysis and molecular dating. The spatial genetic structure and demographic history of 48 individuals of O. handiense were analysed with inter‐simple sequence repeat (ISSR) markers through analyses of molecular variance, Mantel tests, mismatch distributions and bottleneck analyses. The macroclimatic envelope of the species was modelled using an ensemble approach of eight species distribution models, and its suitable areas predicted for extant, past (21 ka) and future (2050, 2080) conditions. Results Orthotrichum handiense was resolved as sister to the Californian O. underwoodii and their most recent common ancestor was dated to early Miocene–Pliocene. ISSR analyses revealed extremely low levels of genetic diversity and provided evidence for a recent bottleneck and for isolation‐by‐distance at the local scale. The different models investigated all pointed to the mismatch between the limited extant distribution and the extent of macroclimatically suitable areas. All models predicted climatic unsuitability on Fuerteventura and Lanzarote at 21 ka, but were conflicting in other areas. A dramatic reduction and loss of suitable areas were predicted for 2050 and 2080, respectively. Main conclusions The phylogenetic position of O. handiense points to a long‐distance dispersal event from a western North American ancestor and emphasizes the differences in the origin of Macaronesian endemic bryophytes and angiosperms. The predicted absence of suitable macroclimatic conditions in Fuerteventura at 21 ka supports the hypothesis of a palaeoendemic origin and a recent founder event in Fuerteventura, consistent with the low levels of genetic diversity and with evidence for a recent bottleneck. While the biogeographical history of the species hence involves major dispersal events over periods of tens of thousands of years, its ability to respond quickly to predicted climate change during the next few decades is questioned.